GRAIN EXPORT OF UKRAINE IN THE CONDITIONS OF WAR - BEZSMERTNA, Oksana; MUSYCA, Yevhenii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines and analyzes the changes that have occurred in the grain market of Ukraine, in particular in the process of its export. An analysis of the dynamics of grain and leguminous export volumes for 2010-2023 was carried out, and a structural analysis of grain exports in 2023 was carried out. A study of the geography of grain export was conducted and trends were revealed regarding the provision of Ukrainian grain to the importing countries that need it most.Since February 2022, the Ukrainian grain market has undergone irreversible changes, the impact of which was not only national, but also international. In the first year of the Black Sea Grain Agreement, grain exports through the humanitarian corridor partially resumed, but many importing countries that previously supplied grain to Ukraine did not receive grain on time and sought alternative supplies.It was found that by July 2023, exports of cereals and pulses had returned to 2014 levels. At the same time, the dominant crop was corn, which accounted for more than 50% of the export structure. Corn had to be sold quickly to make room in the granaries for wheat from the summer harvest.The article also emphasizes that the geography of exports changed significantly during the war. In the conditions of limited supplies through Ukrainian seaports, the neighboring countries of Poland and Romania came to the rescue, allowing the transit of Ukrainian grain. Thus, the share of Ukraine in grain exports to Europe increased from 19.5% in 2020 to 52.2% in 2022.Turkey has also become an important participant in international trade, allowing goods to be transshipped to countries in Africa and the Middle East. In addition, as stated in the article, Turkey, as a grain hub, sent a part of Ukrainian wheat flour in finished form to the African region Since the long-term survival of the concluded Black Sea Grain Initiative was not fully guaranteed, grain-importing countries bought grain during periods of falling export prices and built up stocks to prevent a worsening of the global food crisis.
Keywords: grain; grain crops; export; importing countries; export price; export geography